2016
DOI: 10.32929/2446-8355.2016v25n1p39-54
|View full text |Cite
|
Sign up to set email alerts
|

TRATAMENTOS PRÉ-GERMINATIVOS E SUBSTRATOS NA GERMINAÇÃO DE SEMENTES E BIOMETRIA DE PLÂNTULAS DE Hymenaea courbaril L. var. Stilbocarpa

Abstract: O presente trabalho objetivou testar a influência de tratamentos pré-germinativos e de diferentes substratos na germinação de sementes, biometria de plântulas e teor de clorofila de folhas de jatobá (Hymenaea courbaril). O experimento foi realizado na UNESP, Campus de Ilha Solteira - SP, em casa de vegetação do tipo Pad & Fan, de março a abril de 2011. As sementes foram submetidas aos seguintes tratamentos pré-germinativos: imersão em água por 12 horas, imersão em água por 24 horas, escarificação mecânica,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…(Medeiros e Zanon, 1999), Hymenaea courbaril L. var. Stilbocarpa (Pagliarini et al, 2016), Myracrodruon urundeuva Allemão LC (Guedes et al, 2011), Astronium concinnum Schott (Souza et al, 2012) e Caesalpinia pyramidalis Tul. (LIMA et al, 2011).…”
Section: Resultsmentioning
confidence: 99%
“…(Medeiros e Zanon, 1999), Hymenaea courbaril L. var. Stilbocarpa (Pagliarini et al, 2016), Myracrodruon urundeuva Allemão LC (Guedes et al, 2011), Astronium concinnum Schott (Souza et al, 2012) e Caesalpinia pyramidalis Tul. (LIMA et al, 2011).…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, the morphometry is fundamental to assist in seedling production and area recovery studies (Andrade et al, 2010). Despite its importance, this information is still scarce, taking into consideration the great biodiversity in the Brazilian biomes (Fonseca et al, 2013), andPagliarini et al (2014) described the results of this kind of research as being infrequent. In addition, knowledge about the fruit and seed chemical characteristics also enable indicating their potential use and being able to correlate these characteristics with the seed dispersal processes (Fernandes et al, 2021).…”
Section: Determination Of the Phenolic Compounds Flavonoids Carotenoi...mentioning
confidence: 99%
“…After that, initial evaluations using sand at high temperatures indicated that this substrate was adequate to propitiate better germination rates [9]. Pagliarini et al [40] have mentioned that sandor commercial organic-based substrates are both acceptable to this species germination, even though these methods presented variations in the germination speed index. The present study data contributes to the previous information, that there are no substantial discrepancies between those methods.…”
Section: Substrate Influencementioning
confidence: 99%